I am with you: a netnographic analysis of the Instagram opinion leaders on eating behavior change - Saboia, Inga (2020)
Currently we are strongly influenced by the changes provided by Web 2.0. The number of users consuming and sharing online information about health and wellbeing is increasing. This is a new scenario and a fertile field to study, in which social networks and eHealth applications are powerful tools to support behavior change. This article explores the influence processes of online opinion leaders, such as health professionals and non-professional, on the food behavioral change of their followers on online social networks. We use a netnography observation method following user profiles on Instagram. Some groups and its characteristics and practices were identified. This paper focuses only on three opinion leaders categories: nutritionists, POLs and healthy lifestyle in Portugal and Brazil. Results show different opinion leaders acting as partners, but with different characteristics and practices.